Sex differences in frailty manifestations in patients with coronary artery disease - K. E. Krivoshapova; N. A. Galimova; E. D. Bazdyrev; O. L. Barbarash (Кардиоваскулярная терапия и профилактика)
Aim. To analyze the differences in detection rate of prefrailty and frailty syndrome (FS) in male and female patients with multivessel coronary artery disease (CAD) undergoing elective coronary artery bypass grafting (CABG).Material and methods. The study included 387 patients admitted for elective primary CABG. Screening for prefrailty and FS in patients before surgery was performed using the questionnaire "Age is not a drawback".Results. In the age group of 45 to 59 years, 25% of females and only 6% of males had signs of FS, while 25% of women and 34% of men did not present with signs of frailty and prefrailty. Half of middle-aged women and 60% of middle-aged men had prefrailty. Between the ages of 60 and 74, only 14% of women and 24% of men were not frail. Elderly women are more likely than elderly men to present with signs of FS (p=0,040). The symptoms of prefrailty in elderly patients were detected at equal rate in men and women (59% and 60%, respectively). All senile-aged patients presented with the signs of prefrailty or FS.Conclusion. Patients with multivessel CAD present with manifestation of frailty in senile, elderly, and middle age. At the same time, middle-aged and elderly women with the higher rates of comorbid disorders require special attention.